Mechanistic Insight into Nanoparticle Surface Adsorption by Solution NMR Spectroscopy in an Aqueous Gel. (17th July 2017) - Egner, Timothy K.; Naik, Pranjali; Nelson, Nicholas C.; Slowing, Igor I.; Venditti, Vincenzo
Abstract: Engineering nanoparticle (NP) functions at the molecular level requires a detailed understanding of the dynamic processes occurring at the NP surface. Herein we show that a combination of dark‐state exchange saturation transfer (DEST) and relaxation dispersion (RD) NMR experiments on gel‐stabilized NP samples enables the accurate determination of the kinetics and thermodynamics of adsorption. We used the former approach to describe the interaction of cholic acid (CA) and phenol (PhOH) with ceria NPs with a diameter of approximately 200 nm. Whereas CA formed weak interactions with the NPs, PhOH was tightly bound to the NP surface. Interestingly, we found that the adsorption of PhOH proceeds via an intermediate, weakly bound state in which the small molecule has residual degrees of rotational diffusion. We believe the use of aqueous gels for stabilizing NP samples will increase the applicability of solution NMR methods to the characterization of nanomaterials.